2021
DOI: 10.3390/ani11082308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obesity on Adiponectin System Skin Expression in Dogs: A Comparative Study

Abstract: Obesity is an important health issue in dogs since it influences a plethora of associated pathologies, including dermatological disorders. Considering the scarcity of information in pets, this work aimed to evaluate the localization and expression of adiponectin (ADIPOQ) and its two receptors (ADIPOR1 and ADIPOR2) in the skin of 10 obese dogs, compared with serum ADIPOQ level. Through immunohistochemistry, ADIPOQ and ADIPOR2 were observed in the adipose tissue, sweat and sebaceous glands, endothelium, and some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The “Adiponectin system” term represents the specific, tight, and effective functions and communications between adiponectin source, the adiponectin hormone itself and its receptors on the target cells, which lead specifically to cellular responses in different specific target cells. This term is used widely and commonly in the Endocrine field as proven by many studies in prestigious books and publications [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The biologic effect of certain hormones is subordinated to its interactions with specific high-affinity receptors on the cell membrane or in the cytoplasm or nucleus of target cells.…”
Section: Adiponectin and Its Cellular Receptors Adipors “Adiponectin ...mentioning
confidence: 99%
“…The “Adiponectin system” term represents the specific, tight, and effective functions and communications between adiponectin source, the adiponectin hormone itself and its receptors on the target cells, which lead specifically to cellular responses in different specific target cells. This term is used widely and commonly in the Endocrine field as proven by many studies in prestigious books and publications [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The biologic effect of certain hormones is subordinated to its interactions with specific high-affinity receptors on the cell membrane or in the cytoplasm or nucleus of target cells.…”
Section: Adiponectin and Its Cellular Receptors Adipors “Adiponectin ...mentioning
confidence: 99%
“…If these signaling pathways are impaired, due to, for example, a sterol precursor accumulation, the induction and promotion of the anagen HC phase is impossible, resulting in alopecia [75]. It was found that obesity had a negative impact on HF SCs and can cause hair thinning [76,77]. In our study, 30 out of 100 affected individuals (30%) were identified as overweight, while only 10 out of 116 controls were overweight (11.6%; Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Although the concentrations of serum GLOB and T-BIL were outside the normal reference ranges, the reference range presented in this study is a simple reference value provided by the analysis equipment (Hitachi 7180; Hitachi High-Technologies Co., Tokyo, Japan), and the reference ranges presented in this paper are not absolute criteria for judging whether a dog is clinically and pathologically normal or abnormal. In addition, different standards for the reference range of serum biochemistry in animals are suggested for different research institutions, analysis equipment, and researchers, and it has been argued that different optimal normal ranges should be applied depending on the breed, age, and physiological state, among other factors [ 53 , 54 , 55 ]. When the reference ranges suggested by Fielder [ 53 ] and Dall’Aglio [ 54 ] were applied, the concentrations of serum GLOB and T-BIL in this study were within the normal ranges.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different standards for the reference range of serum biochemistry in animals are suggested for different research institutions, analysis equipment, and researchers, and it has been argued that different optimal normal ranges should be applied depending on the breed, age, and physiological state, among other factors [ 53 , 54 , 55 ]. When the reference ranges suggested by Fielder [ 53 ] and Dall’Aglio [ 54 ] were applied, the concentrations of serum GLOB and T-BIL in this study were within the normal ranges. Furthermore, the experimental dogs in this study were judged to have a normal health condition, under the diagnosis of a professional veterinarian, based on the results of their hematologic and biochemical parameters and clinical health status at the time of trial initiation.…”
Section: Discussionmentioning
confidence: 99%